The effectiveness of Deli Serdang library’s information literacy program on community literacy skills - Surbakti, Khoirunnisa W Rizkiah; Sayekti, Retno (Faculty of Communication, Padjadjaran University, 2025)
Background: Information literacy has become a crucial competency in the digital era, enabling individuals to filter valid and relevant information. Despite increasing internet access, many users are digitally active yet cognitively passive in verifying the information they receive. Deli Serdang Regency continues to face challenges related to low community literacy levels, as reflected in its low Community Literacy Development Index score.Purpose: This study aims to analyze the effectiveness of the information literacy program implemented by the Deli Serdang Library in enhancing community literacy skills.Methods: The research employed a quantitative approach using a one-group pretest-posttest design. The sample consisted of 100 respondents selected through purposive sampling based on specific criteria: having participated in the information literacy program and residing in the Deli Serdang area. Data were collected using a questionnaire, and analyzed using the Paired Sample T-Test to determine differences before and after the program implementation.Results: The information literacy program conducted by the Deli Serdang Library has proven successful in improving community literacy skillsConclusions: The information literacy program effectively fosters critical and responsible thinking in navigating the complex flow of information in the digital age. The study underscores the vital role of libraries as centers for community empowerment through the promotion of a sustainable literacy culture in the digital era.